Review : Kejadian mastitis dan kaitannya dengan vitamin dan Trace Mineral Cu, Zn, Se - yanuartono - yanuartono; Alfarisa Nururrozi; Soedarmanto Indarjulianto; Hary Purnamaningsih; Nurman Haribowo (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2018)
Mastitis means inflammation of the udder and is a common disease among dairy cows worldwide. It is subdivided into clinical mastitis and subclinical mastitis, both influence milk quality and quantity, and mastitis is therefore of major economic concern for the farmer. The incidence rate of mastitis varies between herds and depends on the exposure to pathogens, environmental and management factors and the immune status of the cow. Mastitis is associated with release of free radicals, increased total oxidant capacity and decreased total antioxidants capacity in milk. Vitamin C, E, , α tocopherol, A, β-karoten and trace mineral (Cu, Zn, and Se) feeding, as an antioxidant, in dairy cows have shown appreciable protective effects by reducing the incidence of mastitis.The purpose of this review is to discuss the role of Vitamins C, E, α tocopherol, A, β-carotene, Cu, Zn, and Se in the incidence of mastitis.